Association of a Clinician's Antibiotic-Prescribing Rate With Patients' Future Likelihood of Seeking Care and Receipt of Antibiotics. (10th August 2020) - Shi, Zhuo; Barnett, Michael L; Jena, Anupam B; Ray, Kristin N; Fox, Kathe P; Mehrotra, Ateev
Abstract: Background: One underexplored driver of inappropriate antibiotic prescribing for acute respiratory illnesses (ARI) is patients' prior care experiences. When patients receive antibiotics for an ARI, patients may attribute their clinical improvement to the antibiotics, regardless of their true benefit. These experiences, and experiences of family members, may drive whether patients seek care or request antibiotics for subsequent ARIs. Methods: Using encounter data from a national United States insurer, we identified patients <65 years old with an index ARI urgent care center (UCC) visit. We categorized clinicians within each UCC into quartiles based on their ARI antibiotic prescribing rate. Exploiting the quasi-random assignment of patients to a clinician within an UCC, we examined the association between the clinician's antibiotic prescribing rate to the patients' and their spouses' rates of ARI antibiotic receipt in the subsequent year. Results: Across 232, 256 visits at 736 UCCs, ARI antibiotic prescribing rates were 42.1% and 80.2% in the lowest and highest quartile of clinicians, respectively. Patient characteristics were similar across the four quartiles. In the year after the index ARI visit, patients seen by the highest-prescribing clinicians received more ARI antibiotics (+3.0 fills/100 patients (a 14.6% difference), 95% CI 2.2–3.8, P < 0.001, ) versus those seen by the lowest-prescribing clinicians. The increase in antibiotics was also observed among the patients' spouses. The increase in patient ARI antibiotic prescriptions was largely driven by an increased number of ARI visits (+5.6 ARI visits/100 patients, 95% CI 3.6–7.7, P < 0.001), rather than a higher antibiotic prescribing rate during those subsequent ARI visits. Conclusions: Receipt of antibiotics for an ARI increases the likelihood that patients and their spouses will receive antibiotics for future ARIs. Abstract : We assessed whether receiving an antibiotic changes a patient's future care-seeking behaviors. Patients who receive antibiotics for an acute respiratory illness (ARI) are more likely to seek care for subsequent ARIs and receive more antibiotics in the subsequent year.